Synthetic vectors for gene delivery: An overview of their evolution depending on routes of administration. Issue 9 (3rd June 2015) - Belmadi, Nawal; Midoux, Patrick; Loyer, Pascal; Passirani, Catherine; Pichon, Chantal; Le Gall, Tony; Jaffres, Paul‐Alain; Lehn, Pierre; Montier, Tristan
Abstract Nucleic acid delivery constitutes an emerging therapeutic strategy to cure various human pathologies. This therapy consists of introducing genetic material into the whole body or isolated cells to correct a cellular abnormality or disfunction. As with any drug, the main objective of nucleic acid delivery is to establish optimal balance between efficacy and tolerance. The methods of administration and the vectors used are selected depending on whether the goal of treatment is the production of an active protein; the replacement of a missing or inactive gene; or the combat of acquired diseases, such as cancer or AIDS. In that sense, synthetic vectors represent a valuable solution because they are well characterized, their structure can be fine tuned, and their potential toxicity can be reduced, since toxicity depends on the composition of the formulations. Here we review various synthetic vectors for gene delivery and address the question of their biodistribution as a function of the route of administration. We highlight the modifications to vectors structure and formulations necessary to overcome the major hurdles limiting the effectiveness of nucleic acid therapies.